RMPS, morality & belief - Walker, Joe (Hodder Gibson, 2016)
Cover -- Book title -- CONTENTS -- NOTES TO TEACHERS/LEARNERS -- 1 Morality and belief -- RELIGION AND JUSTICE -- 2 The causes of crime -- 3 Perspectives on punishment -- 4 Approaches to capital punishment -- 5 Sentencing in the UK -- 6 Comparative effectiveness of capital punishment and UK sentencing -- RELIGION AND RELATIONSHIPS -- 7 Religious, moral and legal aspects of marriage -- 8 Nature of relationships: sexuality -- 9 Nature of relationships: love and intimacy -- 10 Perspectives on the roles of men and women -- 11 Gender inequality and exploitation